A escrita e a reescrita no sexto ano do Ensino Fundamental II: uma proposta de intervenção - THEODORO, Nathália Regina Argenau Branco (2018)
This research, developed under the Postgraduate Program in Professional Master's in Literature (PROFLETRAS), a local unit of the Federal University of the Triângulo Mineiro (UFTM), campus of Uberaba / MG, promoted by CAPES, sought to investigate, from the textual productions of class of the 6th grade elementary school, from the public school of the city of Morro Agudo / SP, and the analysis of the Portuguese Didactic Book, adopted at this level of teaching, the need for teaching writing and rewriting to be based on dialogical conception of language, transcending the practice of producing "essays" as a pretext for practicing writing. The general objective is to problematize the process of rewriting as a constituent part of learning writing. Therefore, it adopts the methodological procedures of the didactic sequence proposed by Dolz, Noverraz and Schneuwly (2011). Among twenty-nine texts produced by the students, it is composed of twenty-four texts, belonging to the students who participated in all the rewriting phases. For the analysis, four texts of each produced version were selected, denominated, first textual version (1º VT), first production rewritten (1st PR), second production rewritten (2nd PR) - the fairy tale in reverse. We analyze, in the 1st PR, the semantic levels related to the "what to say" of the student; in the 2nd PR, we analyzed the syntactic, morphological, phonological levels, textual structure and punctuation related to "how to say" (GERALDI, 2013). At each stage of rewriting, the practice of linguistic analysis constituted-as a fundamental platform to reflect on the linguistic resources in operation. It has the theoretical basis Geraldi (2003, 2008, 2013, 2015) and Mendonça (2006) on the teaching of Portuguese Language and the practice of linguistic analysis; Geraldi (2008), Van Dijk (2010) and Propp (2006) in relation to narrative structures, focusing on fairy tales; Geraldi (2013), Garcia (2006), Koch, (2003), Mendonça (2006), among others, regarding the elaboration of workshops. The results of the productions indicate that the contact with varied texts, the workshops elaborated from the difficulties found in the textual productions, and, mainly, the work of intervention with the rewriting by textual-interactive notes, according to Ruiz (2015), made possible significant improvements in the productions of the students and supported the construction of the fairy tale in reverse.